2020
DOI: 10.1161/circinterventions.119.008657
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Drug-Eluting Absorbable Metal Scaffold Restenosis

Abstract: Background: The pathomechanisms underlying restenosis of the bioabsorbable sirolimus-eluting metallic scaffold (Magmaris) remain unknown. Using serial optical coherence tomography, we investigated causes of restenosis, including the contribution of late scaffold recoil versus neointimal hyperplasia. Methods: Patients enrolled in BIOSOLVE-II undergoing serial angiography and optical coherence tomography (post-intervention and follow-up: 6 months and/or 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Interestingly, half of the MgBRS restenosis was caused by scaffold collapse (Figure 6). In another OCT study that included 70 patients with MgBRS failure, the presence of late collapse was found as the main cause of late lumen loss, and device collapse was seen significantly more frequently in patients with fibrotic lesions [81]. These data suggest that future developments of MgBRS should focus on maintaining the radial force of the device for a longer period.…”
Section: Interventional Devicesmentioning
confidence: 92%
“…Interestingly, half of the MgBRS restenosis was caused by scaffold collapse (Figure 6). In another OCT study that included 70 patients with MgBRS failure, the presence of late collapse was found as the main cause of late lumen loss, and device collapse was seen significantly more frequently in patients with fibrotic lesions [81]. These data suggest that future developments of MgBRS should focus on maintaining the radial force of the device for a longer period.…”
Section: Interventional Devicesmentioning
confidence: 92%
“…Even though long-term follow-up showed no scaffold thrombosis up to three years after implantation [ 5 , 31 ], observations of decrease in lumen area assessed with intravascular imaging over time [ 5 , 9 , 32 , 33 ] have raised questions about efficacy and concerns of higher restenosis rates compared to DES [ 6 , 7 , 9 ]. Due to lower radial strength of the MgBRS compared to DES, manipulation and repeated post-dilation after implantation may increase the risk of fracturing and dismantling of the BRS possibly leading to collapse and recoil [ 8 , 9 ]. It should be possible to avoid repeat post-dilatation after placement of the scaffold, if optimal lesion preparation is obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that coronary lesions treated with early generation Magmaris BRS (Biotronik AG, Bülach, Switzerland) (MgBRS) resulted in lumen area reduction within the first year after implantation [ [5] , [6] , [7] ]. The exact mechanism is unclear, but increased plaque burden compromising the scaffold area, increased neointimal formation in the early phase of vascular healing, fast BRS resolution or constrictive remodeling have been considered as contributing factors [ 8 , 9 ]. Due to lower radial strength of the BRS compared to metal stents [ 10 ], repeat post-dilatation after implantation should be avoided, because of increased risk of dismantling causing BRS collapse and recoil.…”
Section: Introductionmentioning
confidence: 99%
“…OCT imaging was performed according to current recommendations ( 22 ) with commercially available OCT systems (Dragonfly DF-OCT-catheter combined with the C7-XRTM imaging system; LightLab Imaging Inc., Westford MA, USA). Pullbacks were assessed for the presence of atherosclerotic plaque features as previously described ( 23 ) and included fibrous, lipid and calcified plaques (see Table 2 ). A total of 222 frames from 51 patients were used for analysis.…”
Section: Methodsmentioning
confidence: 99%